THE ROLE OF SINGLE PARENTS IN DEVELOPING CHILDREN'S EMOTIONAL AND SPIRITUAL INTELLIGENCE IN SUMENEP - Nor Laila; Ach. Firman Ilahi (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2024)
This study seeks to ascertain the role of single moms in the emotional and spiritual intelligence development of children in Errabu Village, Sumenep, as well as the variables that impede this growth. This research employs a qualitative approach utilizing a case study methodology. This study utilizes interviews as primary data sources and significant documents as secondary data sources. The methods of data collection include interviews, observations, and documentation. In this study, data analysis encompasses data reduction, data exposure, and conclusion formulation. This study examines the role of single moms in Errabu Village in fostering emotional intelligence, focusing on the stages of emotional intelligence development and their involvement with children. The job of spiritual intelligence is encouraging children to read scriptures together, elucidating their significance in daily life, assisting in the formulation of their life missions, and engaging them in religious spiritual activities. Nevertheless, among the several responsibilities mentioned, the position of a single mother is significantly limited in fostering the emotional and spiritual intelligence of children in Errabu Village. The constraining elements include heavy work commitments, painful experiences, and overwhelming desires.